Widening the Sphere of Discourse: Reflections on the Feminist Perspective in Religious Studies - Weaver, Mary Jo (Horizons, 1989)
This past February I spent a bracing weekend with two feminist pioneers in their own fields. Joan Huber is an old friend and early mentor, Dean of Social and Behavioral Sciences at Ohio State, and a well-published feminist sociologist. Susan Gubar, my best friend at Indiana University for more than a decade, is a distinguished literary critic and co-author of landmark books like The Madwoman in the Attic, and The Norton Anthology of Literature by Women. Both have changed the shape of their respective disciplines with their work on women and so carry impeccable feminist credentials. Susan and I went to Columbus to help Joan prepare for her March debate with Carol Gilligan.Since I grew up next to Joan as a teenager, weekends with her are always wonderful for me because they combine all the comforts of home with all the things I could never do while growing up. When I go to Joan's house I eat wonderful meals, drink too much, abandon all my resolutions about smoking, stay up too late, and engage in fabulous conversation. Adding Susan to this cluster of stimulants tripled the pleasure, and the fact that it took us hours to get there and forced us to reread Gilligan did not dampen the occasion. I looked forward to the visit and secretly hoped that the conversation would do something to renew my flagging feminist spirit.